DELIVERY ROUTE OF CHAMOMILE ON THE GROWTH AND SUBSEQUENT PHYSIOLOGY OF BROILER CHICKENS UNDER E. COLI CHALLENGE - & Beski, khishtan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This experiment was conducted to investigate the effect of different levels (5g/kg ,10 g/kg or litter) of chamomile flower in feed and water on performance and gut health of broiler chickens under E. coli challenge. A total of 480-day-old Ross 308 broilers were randomly assigned to 12 treatments each replicated 4 times with 10 birds. Oral inoculation with E. coli was on days 8 and 9 of birds age. At day 10 and 35, the interaction (p<0.05) between the experimental factors decreased the feed intake in the challenged birds supplemented with chamomile. At day 10, unchallenged birds were heavier (p<0.05) than the challenged groups. Up to 35 days, birds on antibiotics (zinc bacitracin 360g/kg) and chamomile containing diets were heavier than other groups. The FCR improved in chamomile supplemented birds in both challenge conditions. Challenged birds had poorer FCR than unchallenged birds. The FCR improved in antibiotics and chamomile supplemented birds than those on control diets. The intestinal pH, serum lipid content decreased and serum protein profile improved by chamomile supplementation. The interaction of the experimental factors increased (p<0.0001) protein digestibility in the unchallenged birds supplemented with chamomile in their diets. Protein digestibility improved (p<0.001) in chamomile supplemented birds. The interaction of the experimental factors increased fat digestibility (p<0.0001) in the challenged birds on the lower level of dietary chamomile. Fat digestibility was higher (p<0.0001) but protein digestibility and villi were lower in the challenged birds than unchallenged groups. Longer villi were observed in the unchallenged birds on the lower level of chamomile in their drinking water and those on the highest level of dietary chamomile